The Inhibition of Acetylcholinesterase by Dantrolene and Ondansetron - N’Da, C. I.; Petzer, A.; Petzer, J. P. (Drug Research, 2015)
A virtual screening study has suggested that the skeletal muscle relaxant, dantrolene, and the antiemetic drug, ondansetron, may act as inhibitors of the enzyme acetylcholinesterase (AChE). Based on this proposal, the current study examines the AChE inhibitory properties of these drugs.Using AChE from human erythrocytes as enzyme source, it is shown that dantrolene and ondansetron inhibit AChE with IC50 values of 12.8 µM and 37.1 µM, respectively. For comparison, the reference AChE inhibitors, tacrine and ranitidine, exhibit IC50 values of 0.144 µM and 3.37 µM, respectively. By measuring the recoveries of enzyme activities after dilution of enzyme-inhibitor mixtures, it is further shown that dantrolene and ondansetron act as reversible AChE inhibitors.By considering the typical plasma concentrations of dantrolene and ondansetron in humans at therapeutic doses, the pharmacological relevance of the AChE inhibitory potencies of these drugs is discussed. At typical plasma concentrations, ondansetron is unlikely to inhibit AChE under physiological conditions. The inhibition of AChE by ondansetron is therefore not of clinical relevance in humans. In contrast, after intravenous administration of dantrolene to humans, the typical plasma concentrations reached are similar to the recorded IC50 value for the inhibition of AChE, and dantrolene may thus produce pharmacological significant inhibition of AChE. Further investigation is necessary to clarify the pharmacological relevance of the AChE inhibitory effect of dantrolene.
Keywords: acetylcholinesterase; dantrolene; ondansetron; inhibition; ondansetron